IMPACT OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY - Agha, Hina (European Scientific Journal, ESJ, 2014)
The main purpose of this study is to empirically test the impact of working capital management on profitability .To investigate this relationship between these two, the author collected secondary data from Glaxo Smith Kline pharmaceutical company registered in Karachi stock exchange for the period of 1996-2011. For this purpose, in this study we use variable of return on assets ratio to measure the profitability of company and variables of account receivable turnover, creditors turnover, inventory turnover and current ratio as working capital management criteria. The results of the research show that there is a significant impact of the working capital management on profitability of company. Therefore, managers may enhance the profitability of their firms by minimizing the inventory turnover, account receivables ratio and by decreasing creditors turnover ratios but there is no significant effect of increasing or decreasing the current ratio on profitability. So, the results indicate that through proper working capital management the company can increase its profitability. This study will benefit the Pharmaceutical companies in the management of their working capital in such an efficient manner so that they can multiply their profitability.